A Strategic Global Alliance between Nokia and Microsoft - Aggarwal, Vimal K (Gyan Management Journal, 2010)
Microsoft, founded in 1975, is the worldwide leader in software, services and solutions that help people and businesses realize their full potential. Microsoft has its own mobile platform in the form of Windows Mobile, but it does not have the same reach as Symbian (around 10% market share, compared to 50%).Nokia is a pioneer in mobile telephony and the world’s leading maker of mobile devices. Presently, they are connecting people in new and different ways - fusing advanced mobile technology with personalized services to enable people to stay close to what matters to them. Beside this, they also provide comprehensive digital map information through NAVTEQ; and equipment, solutions and services for communications networks through Nokia Siemens Networks.